On the Origin of the Lithuanian tačiaũ ‘But, However, Yet’ - Ostrowski, Norbert (Lingua Posnaniensis, 2012)
The present study is intended as a further contribution to our knowledge of the origin of the Lithuanian connective tačiaũ ‘but, however, yet’. Of two existing so far etymologies we speak in explanation of Pranas Skardžius. In his opinion tačiaũ traces back to the combination of deictic pronoun tat ‘this, that’ and postpositioned particle jau, strictly speaking jau functioning as an ‘emphatic assertion of identity’. Typological data presented below support such a possibility.